1999
DOI: 10.1152/physiologyonline.1999.14.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Perception in the Gut

Abstract: The ability of the gut mucosa to sense the chemical composition of chyme is important for gastrointestinal functions. The demonstration of gustducin and transducin, two alpha-subunits of GTP-binding proteins involved in gustatory signal transduction, in gastrointestinal epithelial cells provides first clues to the molecular basis of enteric chemosensitivity. Nitric oxide may play a role as a secondary messenger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 13 publications
4
81
1
Order By: Relevance
“…One of the specialized cell types in mammalian gastrointestinal mucosa, the brush cell (also known as tufted or caveolated cell), shares distinct features with the chemosensory taste receptor cells of the tongue. They both have an apical tuft of microvilli and express α-gustducin, the α subunit of the heterotrimeric cGMP-coupled protein involved in bitter transduction in oral taste receptor cells (Hofer et al, 1999;Rozengurt, 2006). Furthermore they all share the NTS as the first central relay and place of integration.…”
Section: Upper Small Intestine: Cck Gip and "Taste In The Gut"mentioning
confidence: 99%
“…One of the specialized cell types in mammalian gastrointestinal mucosa, the brush cell (also known as tufted or caveolated cell), shares distinct features with the chemosensory taste receptor cells of the tongue. They both have an apical tuft of microvilli and express α-gustducin, the α subunit of the heterotrimeric cGMP-coupled protein involved in bitter transduction in oral taste receptor cells (Hofer et al, 1999;Rozengurt, 2006). Furthermore they all share the NTS as the first central relay and place of integration.…”
Section: Upper Small Intestine: Cck Gip and "Taste In The Gut"mentioning
confidence: 99%
“…2E). These microvilli have also been reported to contain villin and fimbrin/plastin [49]. The function of solitary chemoreceptor cells has been examined in greatest detail for those in the nasal cavity, where they appear to respond to the inhalation of irritating substances by initiating protective reflexes, such as sneezing or apnea [47].…”
Section: Espins In the Microvillar Processes Of Other Sensory Cellsmentioning
confidence: 99%
“…Chemical and mechanical signals control motility, secretion and immune defenses in local and/or central neural and/or non-neural pathways (Buchan, 1999;Furness et al, 1999;Furness et al, 2004). It has been suggested that nutrients in the lumen evoke cholecystokinin (CCK), serotonin and ATP release from enteroendocrine and enterochromaffin cells located in epithelia, and these substances act as sensory mediators for sensory neurons (Eastwood et al, 1998;Buchan, 1999;Höfer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%